Emotion and the arts - Hjort, Mette; Laver, Sue, 1961- (Oxford University Press, 1997)
This collection of essays addresses emotion in relation to the arts, and considers such topics as the paradox of fiction, emotion in the pure and abstract arts, and the rationality and ethics of emotional responses. It is aimed at students and scholars of philosophy, literary studies, and art.